Sustainability, growth, and globalization : a social science perspective - Davis, James E. 1940-; Diem, Richard A. (International social studies forum, the series., 2013)
Over the past decade the notion of sustainability has emerged as a precept that has been applied to government, commerce, the environment and technology. This volume will discuss how sustainability is reflected in economics, political science and geography through the lens of socio-economic change and globalization through theoretical and real world perspectives.Using the Costa Rican Cloud Forest community of Monteverde readers will be able to understand how the notion of sustainability has been applied in a community context whose experiences have global implications.